Implementation Corporate Social Responsibility Based on the Perspective of the Fish Farming Community Empowerment Model - Rudy Kurniawan; Ravik Karsidi; Sapja Anantanyu; Sugihardjo Sugihardjo (Journal of International Conference Proceedings (JICP), 2022)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) conducted by PT. Multi Dimensi Kreasi (MDK) in the fish farming empowerment program in the Bokesan Village, Sindumartani Village, Sleman, Yogyakarta. The research method is qualitative. The sampling technique used was purposive sampling, snow ball sampling, and Forum Group Discussion (FGD). Data collection techniques: interviews, observation, and documentation. Data validation technique: method and source triangulation. The data analysis technique uses an interactive model. The results of the study concluded that the model of fish farmer empowerment through CSR PT. MDK is carried out in the following ways: (a) Intensification of aquaculture with MBG innovation; (b) Stages of empowerment, including: awareness, capacity, and empowerment . Keywords: Corporate Social Responsibility, Empowerment, Fish Farmers